Cognitive and behavioral improvement in adults with fragile X syndrome treated with metformin‐two cases. Issue 7 (18th May 2019) - Protic, Dragana; Aydin, Elber Y.; Tassone, Flora; Tan, Maria M.; Hagerman, Randi J.; Schneider, Andrea
Abstract: Background: The majority of individuals with fragile X syndrome (FXS) have intellectual disability, behavioral problems, autism, and language deficits. IQ typically declines with age in boys with the full mutation. The results of preclinical studies demonstrated that metformin, a biguanide used to treat type 2 diabetes, rescues multiple phenotypes of FXS in both Drosophila and mouse models. Preliminary studies of patients with FXS demonstrated improvements in behavior. Methods: Here, we present two cases of individuals who have been treated with metformin clinically for one year. Results: Both patients demonstrated significant cognitive and behavioral improvements. They also improved eating habits and normalization of their weight percentiles. Conclusion: Metformin may be a candidate drug for treatment of several types of symptoms in individuals with FXS. Abstract : We present two cases of individuals with fragile X syndrome (FXS) who have been treated with metformin clinically for one year. Both patients demonstrated significant cognitive and behavioral improvements, and they also improved eating habits and normalization of their weight percentiles. Metformin may be a candidate drug for treatment of several types of symptoms in individuals with FXS.